1983
DOI: 10.1111/j.1476-5381.1983.tb11054.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exaprolol (MG 8823) on epicardial ST‐segment changes in a feline model of acute myocardial ischaemia

Abstract: 3 Exaprolol (1.0mg kg-, intravenously) a potent P-adrenoceptor blocking agent with 'membrane stabilising activity', when given 1 h after the onset of ischaemia, reduced heart rate and LV dP/dt,, and increased LVEDP. These effects were prolonged (i.e. little recovery in heart rate 3 h after administration). 4 Exaprolol decreased total ST-segment elevation immediately after administration; this was significantly different from the effect of intravenous saline and lasted for at least 3 h. The effects appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The fact that, in those studies, the administration of exaprolol resulted in P-adrenoceptor blockade without significant myocardial depression and reduced at least one index of myocardial ischaemia suggested that this compound might have potential in the early therapy of acute myocardial infarction (Parratt & Udvary 1983). The main purpose of the present studies was to examine the myocardial effects of exaprolol in more detail and to investigate a possible protective effect against early ischaemia-induced ventricular arrhythmias.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The fact that, in those studies, the administration of exaprolol resulted in P-adrenoceptor blockade without significant myocardial depression and reduced at least one index of myocardial ischaemia suggested that this compound might have potential in the early therapy of acute myocardial infarction (Parratt & Udvary 1983). The main purpose of the present studies was to examine the myocardial effects of exaprolol in more detail and to investigate a possible protective effect against early ischaemia-induced ventricular arrhythmias.…”
mentioning
confidence: 85%
“…follow coronary artery occlusion in anaest x etized rats. of 9.8 for the inhibition of t R e inotro ic and chronotropic responses of guinea-pig isolated Exaprolol (MG 8823), a cyclohexylphenol, with &blocking and local anaesthetic properties (Carissjmi et al 1976), has been recently shown to reduce epicardial ST-segment elevation when administered after the induction of myocardial ischaemia in anaesthetized cats (Parratt & Udvary 1980, 1983.…”
mentioning
confidence: 99%